HPV11 targeting PPARA regulates the autophagy to inhibit the occurrence and development of nasal inverted papilloma - Zhu, Gaohan; Zheng, Liying; He, Weining; Chen, Xiaoping; Huang, Shuixian; Jin, Mingming; Zhang, Yi (Frontiers in Oncology, 2026)
IntroductionNasal inverted papilloma (NIP) is closely associated with human papillomavirus (HPV) infection, with HPV11 showing the highest expression levels in NIP tissues. However, the mechanism of its genomic integration remains incompletely understood. This study investigated frequent viral integration at the peroxisome proliferator-activated receptor alpha (PPARA) gene locus—a known regulator of autophagy—and its potential role in HPV11-mediated pathogenesis.MethodsHigh-throughput sequencing of HPV-positive specimens identified PPARA as a common integration site. HPV11 E6/E7 overexpression, PPARA overexpression, and PPARA knockdown models were established in human nasal epithelial cells (HNEpC). Cell proliferation, migration, and autophagy levels were assessed. The role of PPARA in proliferation and autophagy modulation was further validated using a nude mouse xenograft model. Additionally, the autophagy inhibitor 3-Methyladenine (3-MA) was applied to evaluate its effects on proliferation and migration.ResultsHPV11 E6/E7 overexpression significantly enhanced cell proliferation and migration. In contrast, PPARA overexpression promoted autophagy and suppressed proliferation and migration. Inhibition of autophagy by 3-MA reversed the suppressive effects mediated by PPARA. In vivo experiments confirmed the proliferative role of HPV11 E6/E7 and the autophagy-modulating function of PPARA.DiscussionHPV11 exerts dual effects on nasal mucosal cells: promoting proliferation and migration via E6/E7, while concurrently inducing an inhibitory effect through PPARA-mediated autophagy activation. The suppression of autophagy reversed the PPARA-driven inhibition, indicating a key role for the autophagy pathway. These findings suggest that PPARA targeting may be crucial in the pathogenesis of NIP, highlighting a complex interaction between HPV11 integration and host autophagy regulation.